Analysis of the influence of driving modes in a hybrid vehicle on fuel consumption optimization and learning strategies during urban trips - Lopez-Chila, Roberto; Abad-Correa, Anderson; Cruz-Zavala, Héctor De La (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the influence of different driving modes on vehicle efficiency and emissions, focusing on fuel consumption per kilometer traveled during urban trips in Guayaquil, Ecuador. A 2022 Toyota Corolla Hybrid was used for testing, following the SAE J1321:2012 Standard, which provides a standardized method for fuel consumption evaluation. Real-time data collection was conducted using the OBDLINKMX+ device and the GPS Speedometer application. The research evaluates the effects of eco, sport, and normal driving modes on energy efficiency, CO₂ emissions, and overall driving behavior. Results indicate that eco mode significantly reduces fuel consumption and emissions, whereas sport mode enhances driving dynamics but increases fuel use and pollutant output. Normal mode provides a balance between efficiency and performance but lacks optimization for sustainability. The findings highlight the importance of adaptive driving strategies and intelligent vehicle systems in promoting environmental sustainability. Additionally, the study suggests that implementing eco-friendly driving technologies can enhance energy efficiency and reduce the automotive sector’s environmental impact. These insights can guide automotive manufacturers, policymakers, and drivers in adopting strategies that optimize fuel efficiency and minimize emissions. Future research should explore real-time adaptive control systems to further improve driving efficiency and sustainability.